Pengaruh Infrastruktur Pedesaan Terhadap Produktivitas Pangan di Kecamatan Titehena Kabupaten Flores Timur - Katharina Martha Apriliani Wenggol; Fransina W. Ballo; Maria Indriyani Hewe Tiwu (Universitas 45 Surabaya, 2024)
This study aims to find out and explain the influence of rural infrastructure on food productivity in Titehena District, East Flores Regency. The type of research used by the researcher is quantitative research using primary data. The sampling technique used in this study is by using a questionnaire. The data analysis techniques used include validity tests, reliability tests, multiple regression analysis, instrument tests, and hypothesis tests using SPSS analysis tools. The results of this study show that the results of multiple regression testing, partially the accessibility infrastructure variable affects food productivity, the agricultural infrastructure variable affects food productivity, and simultaneously the accessibility infrastructure variable and the agricultural infrastructure variable simultaneously affect food productivity in Titehena District, East Flores Regency.